A small cereal with big promise - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Hungry rice (Digitaria exilis) has been largely neglected by scientists and plant breeders in the past, but it is now being reappraised. Now that consumers have shown that they value it as a food crop, plant breeders are making use of genetic...